Self-management of change processes in educational centers - Vázquez, María Inés (2013)
This paper addresses the self-management processes of change, referring to a series of processes that take place in education centers undergoing change. The perspective from which the approach is proposed is educational management. The evidences integrated into the document are the result of a study conducted in Uruguay, which involved seven primary, secondary, and technical schools. The approach used has been the study of multiple cases with the intention of analyzing the phenomenon in specific contexts, integrating the possibility of studying it from a global perspective. The overall objective was to achieve greater understanding of the self-evaluation and change processes in schools. Within the specific objectives we highlight: to identify the possible links between self-assessment and decision making